2021
DOI: 10.1002/chem.202005124
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization of Spirocyclic λ3‐Iodanes and Their Application to Prepare 4,1‐Benzoxazepine‐2,5‐diones and 1,3‐Diynes

Abstract: Herein, a [3+2] cycloaddition of aza‐oxyallylic cations with ethynylbenziodoxolones for synthesis of new λ3‐iodanes containing spirocyclic 4‐oxazolidinone has been developed. This cyclic λ3‐iodanes display stability in air and excellent solubility in organic solvent. Using them as substrate, both the 4,1‐benzoxazepine‐2,5‐diones and symmetrical 1,3‐diynes derivatives were afforded in high yield under copper(I)‐catalyzed conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…At the outset of our studies, spiro−EBXs 1 a and 4‐methoxybenzenethiol 2 a were employed as the model substrate to optimize the reaction conditions, and the screening results were summarized in Table 1. Based on previous work, [9a,28,29] CuI catalyst was used for the cross‐coupling reaction of iodobenzene with benzenethiol. Different bases were examined, such as, Et 3 N, KO t Bu and Cs 2 CO 3 by using CuI as catalyst in the solvent of dichloromethane (DCM) at 50 °C for 2 hours (entries 1–3), yielding 3 aa from 50 % to 75 %, and 4 aa in 99 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…At the outset of our studies, spiro−EBXs 1 a and 4‐methoxybenzenethiol 2 a were employed as the model substrate to optimize the reaction conditions, and the screening results were summarized in Table 1. Based on previous work, [9a,28,29] CuI catalyst was used for the cross‐coupling reaction of iodobenzene with benzenethiol. Different bases were examined, such as, Et 3 N, KO t Bu and Cs 2 CO 3 by using CuI as catalyst in the solvent of dichloromethane (DCM) at 50 °C for 2 hours (entries 1–3), yielding 3 aa from 50 % to 75 %, and 4 aa in 99 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…[25c] Very recently Kang et al ( 2021) developed spirocyclic iodanes 41 containing 4-oxazolidinone ring through [3 + 2]-cycloaddition between aza-oxyallyl cations and carbonyl group of benziodazolone core in the presence of Cs 2 CO 3 in DCE solvent with good to excellent yield (Scheme 12). [26] Moreover, a trace amount of nitrogen substituted EBXs 41' was also obtained. It was found that synthesized λ 3 -iodanes 41 showed significant stability in air and various organic solvents (DMF, DCM, CH 3 CN, CHCl 3 and CH 3 OH).…”
Section: [3 + 2]-cycloaddition Reactionsmentioning
confidence: 98%
“…24 b In recent years, we studied the role of N -tosylhydrazones 25 and hypervalent iodine reagents in organic synthesis. 26 Therefore, we question whether the “waste” p -toluenesulfonyl anion and iodoarene could be captured in the reaction of N -tosylhydrazones with diaryliodonium salts to yield N -arylpyrazoles and an extra diaryl sulfone, which may be an alternative pathway to take full advantage of substrates (Scheme 1, bottom). To our knowledge, this is the first example to take full advantage of the “waste” part of both N -tosylhydrazones and diaryliodonium salts for constructing two valuable compounds.…”
Section: Introductionmentioning
confidence: 99%